In Rhodotorula mucilaginosa, active oxidative metabolism increases carotenoids to inactivate excess reactive oxygen species - Mosqueda-Martínez, Edson; Chiquete-Félix, Natalia; Castañeda-Tamez, Paulina; Ricardez-García, Carolina; Gutiérrez-Aguilar, Manuel; Uribe-Carvajal, Salvador; Mendez-Romero, Ofelia (Frontiers in Fungal Biology, 2024)
Carotenoids produced by bacteria, yeasts, algae and plants inactivate Free Radicals (FR). However, FR may inactivate carotenoids and even turn them into free radicals. Oxidative metabolism is a source of the highly motile Reactive Oxygen Species (ROS). To evaluate carotenoid interactions with ROS, the yeast Rhodotorula mucilaginosa was grown in dextrose (YPD), a fermentative substrate where low rates of oxygen consumption and low carotenoid expression were observed, or in lactate (YPLac), a mitochondrial oxidative-phosphorylation (OxPhos) substrate, which supports high respiratory activity and carotenoid production. ROS were high in YPLac-grown cells and these were unmasked by the carotenoid production-inhibitor diphenylamine (DPA). In contrast, in YPD-grown cells ROS were almost absent. It is proposed that YPLac cells are under oxidative stress. In addition, YPLac-grown cells were more sensitive than YPD-grown cells to menadione (MD), a FR-releasing agent. To test whether carotenoids from cells grown in YPLac had been modified by ROS, carotenoids from each, YPD- and YPLac-grown cells were isolated and added back to cells, evaluating protection from MD. Remarkably, carotenoids extracted from cells grown in YPLac medium inhibited growth, while in contrast extracts from YPD-grown cells were innocuous or mildly protective. Results suggest that carotenoid-synthesis in YPLac-cells is a response to OxPhos-produced ROS. However, upon reacting with FR, carotenoids themselves may be inactivated or even become prooxidant themselves.